Characteristics of Na2CO3-catalyzed water-gas shift reaction under coal liquefaction conditions. (15th November 2018) - Li, Huan; You, Quan; Wu, Shiyong; Wu, Youqing; Huang, Sheng; Gao, Jinsheng
Highlights: The Na2 CO3 -catalyzed water-gas shift reaction under coal liquefaction conditions was investigated. The formic acid and oxalate acid as intermediate products were detected. Na2 CO3 and water had a synergistic effect on water-gas shift reaction. A major catalyzed mechanism about intermediate products was investigated preliminarily. Abstract: The characteristics of Na2 CO3 -catalyzed water-gas shift reaction (WGSR) under coal liquefaction conditions were investigated. The reactivity of WGSR could be enhanced by improving water content and initial pressure of CO, owing to the reduced activation energy for WGSR in the high water density and subcritical state. The Na2 CO3 had a promoting effect on WGSR, and a synergistic effect between Na2 CO3 and water occurred obviously. HCOONa and NaHCO3 as intermediate products were generated for CO consumption, and subsequently decomposed into CO2 and H2, which can be a hydrogen source further. A major catalyzed mechanisms in WGSR about intermediate products under coal liquefaction conditions was investigated preliminarily.